2012
DOI: 10.1371/journal.pone.0040666
|View full text |Cite
|
Sign up to set email alerts
|

Risks Associated with High-Dose Lactobacillus rhamnosus in an Escherichia coli Model of Piglet Diarrhoea: Intestinal Microbiota and Immune Imbalances

Abstract: Probiotic could be a promising alternative to antibiotics for the prevention of enteric infections; however, further information on the dose effects is required. In this study, weanling piglets were orally administered low- or high-dose Lactobacillus rhamnosus ACTT 7469 (1010 CFU/d or 1012 CFU/d) for 1 week before F4 (K88)-positive Escherichia coli challenge. The compositions of faecal and gastrointestinal microbiota were recorded; gene expression in the intestines was assessed by real-time PCR; serum tumour n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 63 publications
5
122
0
4
Order By: Relevance
“…Current results points to the hypothesis that possibly the dosage for best growth performance is not the same as the best dosage for the prevention of infection breaks. Higher dosages may enhance changes in the microbiota and/or immune responses (Li et al, 2012), consequently increasing the energy expenditure, at expenses of growth. Other recent studies on bacterial consortia in rainbow trout juveniles observed an improvement on growth rate and FCR at 1.5 g/kg dietary probiotic supplementation, but not at 3 g/kg (Ramos et al, 2015) and at 1 g/kg but not at and 5 g/kg (Giannenas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Current results points to the hypothesis that possibly the dosage for best growth performance is not the same as the best dosage for the prevention of infection breaks. Higher dosages may enhance changes in the microbiota and/or immune responses (Li et al, 2012), consequently increasing the energy expenditure, at expenses of growth. Other recent studies on bacterial consortia in rainbow trout juveniles observed an improvement on growth rate and FCR at 1.5 g/kg dietary probiotic supplementation, but not at 3 g/kg (Ramos et al, 2015) and at 1 g/kg but not at and 5 g/kg (Giannenas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is an in vitro study by Kim et al (2012), where the pre-treatment of THP-1 cells with L. plantarum gDNA and their subsequent stimulation with LPS resulted in suppression of TLR2, TLR4, TLR9 and NF-κB transcripts. On the other hand, in their in vivo study Li et al (2012) showed that the preventive administration of L. rhamnosus ACTT 7469 to weanlings for one week followed by ETEC infection led to a significant upregulation of TLR2 and to a statistically not significant reduction of TLR4 and TLR5 mRNA in the jejunum of the pigs treated. However, differences between the results of each experimental study are due to various factors such as the type of experimental scheme (in vitro or in vivo), the type and concentration of the probiotic strain applied, and the developmental level of pigs (sucklings/ weanlings) in the case of in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
“…Even though there are several studies focusing on the effect of probiotic lactobacilli on TLR levels during porcine colibacillosis (Kim et al, 2012;Li et al, 2012), this area of the study is not sufficiently covered, and in the case of combined treatment with n-3 PUFAs studies are fully absent. However, the results presented here are in correlation with cytokine gene expression analysis from a previous experiment (Chytilová et al, 2013), for example: down-regulation of TLR2, TLR5 and NF-κB, and decrease of pro-inflammatory cytokine mRNA (IL-1α, found in the L and LMK groups; increase of TLR4 transcript, induced by flaxseed oil, and up-regulation of both inflammatory mediators (IL-1α, IL-8) detected in the jejunum of the same piglets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies in gnotobiotic mice have significantly advanced our understanding of the important role of microbiota in the intestinal development and homeostasis and the function of the immune system [106][107][108]. We now know that the microbiota is involved in various processes that are beneficial to the host [109], such as fermentation and conversion of food or feed components [110,111], production of essential nutrients and metabolites [109,112,113], maturation and modulation of the immune system [107,114], and colonization resistance against pathogens (see below) [50].…”
Section: Chaptermentioning
confidence: 99%
“…We hypothesise that modulation of the microbiota during the early life of a piglet may be used to reduce the risk of S. suis associated invasive post-weaning disease. Currently, similar approaches with probiotic supplements are being used in pigs to improve animal performance and overall health, although for most applications the underlying mechanism of action that confers the benefits is unknown [106][107][108][109].…”
Section: Effects Of Amps On Host Cellsmentioning
confidence: 99%